Higher ETCOc predicts longer phototherapy treatment in neonatal hyperbilirubinemia - Zhan, Yuan-Li; Peng, Hai-Bo; Jin, Zhen-Chao; Su, Jin-Feng; Tan, Xiang-Yu; Zhao, Lu; Zhang, Lian (Frontiers in Pediatrics, 2023)
Objective This study aimed to evaluate the predictive performance of end-tidal carbon monoxide corrected to ambient carbon monoxide (ETCOc) values phototherapy in neonates with significant hyperbilirubinemia. Methods A prospective study was conducted on neonates with significant hyperbilirubinemia who received phototherapy between 3 and 7 days of life. The breath ETCOc and serum total bilirubin of the recruited infants were measured on admission. Results The mean ETCOc at admission in 103 neonates with significant hyperbilirubinemia was 1.70 ppm. The neonates were categorized into two groups: phototherapy duration ≤72 h (n = 87) and >72 h (n = 16) groups. Infants who received phototherapy for >72 h had significantly higher ETCOc (2.45 vs. 1.60, P = 0.001). The cutoff value of ETCOc on admission for predicting longer phototherapy duration was 2.4 ppm, with a sensitivity of 62.5% and specificity of 88.5%, yielding a 50% positive predictive value and a 92.7% negative predictive value. Conclusion ETCOc on admission can help predict the duration of phototherapy in neonates with hyperbilirubinemia, facilitate clinicians to judge disease severity, and make clinical communication easier and more efficient.